2021
DOI: 10.3389/fimmu.2021.803037
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization and Its Role in Liver Disease

Abstract: Macrophages are important immune cells in innate immunity, and have remarkable heterogeneity and polarization. Under pathological conditions, in addition to the resident macrophages, other macrophages are also recruited to the diseased tissues, and polarize to various phenotypes (mainly M1 and M2) under the stimulation of various factors in the microenvironment, thus playing different roles and functions. Liver diseases are hepatic pathological changes caused by a variety of pathogenic factors (viruses, alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
218
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(228 citation statements)
references
References 295 publications
(355 reference statements)
5
218
0
5
Order By: Relevance
“…The production of another nine chemokines, including CCL1, CCL7, CCL17 and others, was decreased once N-SREBP was overexpressed ( Figure 4H ). However, the production of IFNγ, IL-4 and IL-10, which are canonical cytokines that stimulate M1 or M2 polarization ( Wang et al, 2021 ), as well as 10 other kinds of cytokines, showed no significant conversion between the eGFP- and N-SREBP-overexpressing groups ( Figure 4I ). These data clarified that SREBP could promote the secretion of various inflammatory cytokines in macrophages to fight HTNV infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of another nine chemokines, including CCL1, CCL7, CCL17 and others, was decreased once N-SREBP was overexpressed ( Figure 4H ). However, the production of IFNγ, IL-4 and IL-10, which are canonical cytokines that stimulate M1 or M2 polarization ( Wang et al, 2021 ), as well as 10 other kinds of cytokines, showed no significant conversion between the eGFP- and N-SREBP-overexpressing groups ( Figure 4I ). These data clarified that SREBP could promote the secretion of various inflammatory cytokines in macrophages to fight HTNV infection.…”
Section: Resultsmentioning
confidence: 99%
“…The classical inflammatory activation pattern of macrophages (M1 polarization) or monocytes (M1-like monocytes), which is stimulated by host Th1-type cytokines (such as interferon-γ/IFNγ and tumor necrosis factor-α/TNFα) or pathogen-associated molecular patterns (PAMPs) via JAK/STAT, NF-κB or pattern-recognition receptor (PRR)-mediated signaling, maintains the potential ability of the immune system to restrict viral infection and promote virus clearance by initiating a robust interferon-centered inflammation response, the dysregulation of which triggers a cytokine storm and aggravates host immunopathological injury ( McNab et al, 2015 ; Merad and Martin, 2020 ; McGonagle et al, 2021 ). Alternatively, macrophages can be M2-polarized by Th2-type cytokines (such as IL-4 and IL-10), which promote the resolution of inflammatory responses and assist in tissue repair ( Wang et al, 2021 ). It has been reported that hantavirus (strain no.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical relevance analysis also indicated that high expression of CCL15 or the M2-like macrophage marker CD163 predict a poor prognosis of HCC and the combined predictive value of CCL15 and CD163 in the prognosis is superior to that using either marker alone. Currently, macrophage polarization involves a variety of molecular mechanisms, including TLR4/NF-κB, JAK/STATS, TGF-β/SMADS, PPARγ, NOTCH and microRNA signaling pathways 56 , however, the detailed mechanism driving M2-like macrophages by CCL15 will be our future work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, KCs are activated into M1 phenotype by lipopolysaccharide (LPS), IFN-gamma or M-CSF, characterizing by highly expressing pro-inflammatory genes IL1B, TNFα and iNOS ( 36 ). While IL4 or GM-CSF may polarize KCs into M2 type that highly express ARG1, IL10 and MRC1 ( 27 , 28 ). However, later studies found that M1-M2 dichotomy is insufficient to classify KCs, especially in liver injury ( 37 , 38 ).…”
Section: Kc In Homeostasismentioning
confidence: 99%